Human meningitis due to Streptococcus suis in Lomé, Togo: a case report. Issue 1 (December 2016) - Prince-David, Mireille; Salou, Mounerou; Marois-Créhan, Corinne; Assogba, Komi; Plainvert, Céline; Balogou, Koffi; Poyart, Claire; Tazi, Asmaa
Abstract Background Streptococcus suis is a zoonotic pathogen which represents the leading cause of meningitis in Southeast Asia and an emerging pathogen in the Western world, the main risk factor for infection being contact with pigs. In Africa, the prevalence ofS. suis infections in swine and humans is largely unrecognized, with only one recent report of a limited case series. Case presentation We describe a human case of meningitis due toS. suis in a 32-year-old man living in Togo. The patient had no particular medical history and no risk factors for immunodeficiency but reported regular contact with pork products. Using specific immunological and molecular methods, we characterized the isolate asS. suis serotype 2, ST1, one the most prevalent and virulent clone worldwide. The outcome was favorable after one week of adapted antibiotic therapy but the patient was left with severe hearing disorders. Conclusions This work highlights the emergence of this pathogen in Africa and reinforces the need for accurate epidemiological and surveillance studies ofS. suis infections and for educating clinicians and exposed groups in non-endemic countries.